Penggunaan Beberapa Sumber dan Dosis Aktivator Organik Untuk Meningkatkan Laju dekomposisi Kompos Tandan Kosong Kelapa Sawit - Rapika Tanti Harahap; T. Sabrina; Posma Marbun (Jurnal Agroekoteknologi, 2015)
This research aim to determine the effect of several source and dosage of organic activators ondecomposition rate of empty fruit bunch. This study used a factorial randomized block design (RBD)consist of two factors and three replications. The first factor was the source of organic activatorsconsist of three treatments (chicken manure, cow manure, goat manure) and the second factor wasthe dosage of activator consist of 4 treatments (0, 15, 30 and 45% (w/w)). The results showed thatthe best organic activator in decreasing C/N ratio of compost was chicken manure, withdecomposition rate 10,77 unit/week. The best dosage activator in decreasing C/N ratio of compostwas 45% (w/w), with decomposition rate 17,51 unit/week. Increasing dosage of activator increasedthe decomposition rate, except for chicken manure. The best dosage of chicken manure to increasedecomposition rate of EFB was 30% (w/w).Key words : Oil palm empty bunche compost, organic activator, decomposition rate.